MEDIA PROPAGANDA TECHNIQUES IN THE SOUTH CHINA SEA DISPUTE - Cheryl Pricilla Bensa; Lupita Wijaya (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2017)
Bilateral relationship between Indonesia and China which is a pivotal pathway to Global Maritime Axis’s foreign policy has been relentlessly addressed by President Joko Widodo since his early administration in 2014. However, Indonesia is aware that China’s claim of nine-dashed line (9DL) has overlapped with Indonesia’s sovereignty area, Natuna water. This territory dispute has pushed Indonesian government to take a decisive action by sending a verbal note protest to the Chinese embassy in Indonesia. In the perspective of international communication, this action has scrutinized the interdependence between media systems and political systems as a form of a symbiosis connecting and creating perceptions on the issue. Propaganda techniques of mass media, such as inter alia, name-calling, glittering generality, transfer, plain folks, testimonial, selection, bandwagon, and frustration of scapegoat, might create certain perceptions. This study maps the propaganda techniques by Indonesian high-circulated newspaper Kompas and China’s state-run media Xinhua news agency. This study applies quantitative content analysis method in the period of May 30 to July 30, 2016.